A folk theory of the EEC: popular euroscepticism in the early 1980s. Issue 4 (2nd October 2021) - Moss, Jonathan; Clarke, Nick
ABSTRACT: The 2016 EU Referendum has renewed the focus of historians and social scientists on Britain's historical relationship with Europe as they aim to develop a better understanding of 'the road to Brexit'. The development of Euroscepticism in Britain has often been approached from an elite perspective, with a focus on the conflicting ideas and arguments between politicians, political parties, and the media. This article builds on existing studies by focusing on popular attitudes to Europe during the early 1980s. We analyse responses to a 'special directive' issued by the Mass Observation Project in the autumn of 1982 to mark the ten-year anniversary of Britain joining the European Economic Community (EEC). Reading this previously overlooked material for categories, storylines, and other cultural resources, we identify four key grievances MO panellists shared as common-sense evaluations of Britain's membership of the EEC. We argue these grievances constituted a wider folk theory of Euroscepticism circulating in British society six years prior to Margaret Thatcher's Bruges speech and subsequent debates about further integration in the early 1990s. In developing this argument, we contribute a better understanding of the content and origins of popular Euroscepticism in the 1980s.